Co-production of cement and carbon nanotubes with a carbon negative footprint. (March 2017) - Licht, Stuart
Highlights: Conventional and C2CNT (or CO2 to carbon nanotube) cement plants are compared. The conventionalplant emits 1.1 ton of CO2 per ton cement produced. The C2NT plant emits no CO2 & converting it to a valuable CNT co-product (CNTs). In the C2CNT plant CNTs are produced by molten carbonate electrolysis of CO2 . Abstract: C2CNT (CO2 to carbon nanotube) cement plants are introduced and analyzed with a significant economic incentive to eliminate current plant CO2 greenhouse gas emissions. The exhaust from partial and full oxy-fuel cement plant configurations are coupled to the inlet of a C2CNT chamber in which CO2 is transformed by electrolysis in a molten carbonate electrolyte into CNTs at a steel cathode and pure oxygen at a nickel anode that is looped back in improving cement line energy efficiency and production rate. A partial oxy-fuel process looping O2 back through the plant calcinator has been compared to a full process in which it enters through the plant kiln. The first provides easier retrofit; the second maximizes efficiency by minimizing N2 throughput. Providing an economic impetus to carbon dioxide removal, per ton CO2 avoided the C2CNT cement plant consumes $50 electricity, emits no CO2, and produces $100 cement and ∼$60, 000 of CNTs.